Prayer for the Dead While in Coffin, and Burying in It: A Jurisprudential Study - Al-thyabi, Turki Saud (Journal of Islamic Sciences, 2022)
I spoke in this research about two issues: the prayer for the dead while he is in the coffin, and burial in it, and I made it into an introduction, a prelude, and two chapters. First: I mentioned in it the sayings of the fuqaha’ regarding the ruling on praying for the dead while he is in the coffin, and their evidence. Second topic: the four schools of jurisprudence have agreed - in general - that it is disliked to bury the dead in a coffin without a need. Rather, there was consensus on it, and I talked about burial in the coffin when necessary or needed. I mentioned examples of that, then I followed it up by mentioning the question of who recommended being buried in a coffin. And that his will is not executed unless there is a need to do so, in which case it will be from his capital. I have followed the inductive-analytical method. I appended the research with a conclusion in which I mentioned the most important results, including: It is not known that the deceased was placed in a coffin during the era of the Prophet PBUH, nor his companions.